2008
DOI: 10.1007/s10470-008-9233-2
|View full text |Cite
|
Sign up to set email alerts
|

An implanted system for multi-site nerve cuff-based ENG recording using velocity selectivity

Abstract: This paper describes the design of an implantable system for velocity-selective electroneurogram (ENG) recording. The system, which relies on the availability of multielectrode nerve cuffs (MECs) consists of two CMOS ASICs. One ASIC called the electrode unit (EU) is a mixed analogue/digital signal acquisition system which is mounted directly on an MEC in order to optimize the interface between the two. It is linked to the other ASIC by means of a 5-core cable through which it receives power and commands in add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 21 publications
0
20
0
Order By: Relevance
“…While it is possible to calculate CV using only a single pair of electrodes (a dipole) it has been shown that the velocity selectivity of a system can be increased by using multiple electrodes [2]. The use of velocity selective recording (VSR) enables discrimination of action potentials based both on direction of propagation (afferent or efferent) and CV, without the need to submit the nerve to invasive and potentially damaging procedures [3], [4]. This method provides a viable interface for neural recording systems that have potential use in a range of prosthetic devices.…”
Section: Introductionmentioning
confidence: 99%
“…While it is possible to calculate CV using only a single pair of electrodes (a dipole) it has been shown that the velocity selectivity of a system can be increased by using multiple electrodes [2]. The use of velocity selective recording (VSR) enables discrimination of action potentials based both on direction of propagation (afferent or efferent) and CV, without the need to submit the nerve to invasive and potentially damaging procedures [3], [4]. This method provides a viable interface for neural recording systems that have potential use in a range of prosthetic devices.…”
Section: Introductionmentioning
confidence: 99%
“…To these signals controlled amounts of uncorrelated additive white Gaussian noise were added [3]. Blocks 2 and 3 are the two principal sections of a neural recording system intended for ultimate implantation as a pair of remotely powered modules connected together using a multicore implantable cable [7]. Block 2 is referred to as the electrode unit and is intended to be mounted on the MEC for optimum performance.…”
Section: A System Description 1) Conventional Vsr Signal Processing:mentioning
confidence: 99%
“…It consists of a set of speciallydesigned low noise differential amplifiers (nominal gain 10,000) whose 10 bipolar (or single differential) outputs are digitized (10 bits resolution) and multiplexed into one channel for transmission along the implantable cable [6]. In a distributed sensor architecture, several electrode units are placed at different sites in the peripheral nervous system and connected by implanted cables to a single monitoring unit [7]. The monitoring unit is a demultiplexer (DEMUX) and digital signal processing system that interfaces with an RF telemetry system (not described in this paper).…”
Section: A System Description 1) Conventional Vsr Signal Processing:mentioning
confidence: 99%
See 2 more Smart Citations